POWER OF MEDIA IN INDUSTRIALIZATION OF BALINESE POP MUSIC - Ardini, Ni Wayan; Wirawan, A.A Bagus; Suarka, I Nyoman; Sugiartha, I Gede Arya (E-Journal of Cultural Studies; Vol 8 No 4 (2015): Volume 8, Number 4, November 2015, 2015)
The development of technology, the economic system, and the culture of new music, has caused the Balinese pop music to be industrialized since 1990s. The existence of many recording studios and musicians (composers, singers, and music players) and many other related products all over Bali has also contributed to this. Through the recording products, various types of direct performances and so forth have caused the Balinese pop music to be the commodity of the capitalistic pop culture which is preferred by society. Such industrialization is formed by the power of media (musicians), capitalistic power (the capital owner such as the producer/recording studio owner), and the power of media. This present study was conducted in order to identify the phenomenon of one of three powers in such industrialization, namely, the power of media, especially television. The result of the study shows that the power of television media in the industrialization of the Balinese pop music is the resource which contributes to the distribution of products which are produced for the market or the prospective market in Bali. The television studio which plays the greatest role is the Bali TV. It was established in 2002, namely, the year when the political decentralization in Indonesia started, following the reformation era which started in 1998. Through the regional autonomy, the ethnical local cultures in Indonesia, including the Balinese pop music, were empowered. The Bali TV with “Ajeg Bali” as its ideology has what is called “Klip Bali”, “Tembang Bali” (100% local)”, and “Samatra Artis Bali” programs. The viewers from all over Bali like such programs very much. The more often they are presented (viewed and listened to), the more the Balinese pop music products obtain the promotional and marketing value. A great number of products, including the Balinese pop music, are continuously introduced to the society. The power of media has developed into capitalism and the Balinese community has become the object of its consumption.
Keywords: power of media, Balinese pop music, electronic media, television.